Shared genetic links between hypothyroidism and psychiatric disorders: evidence from a comprehensive genetic analysis - Zhou, Jianlong; Zhu, Lv (Frontiers in Endocrinology, 2024)
Epidemiologic studies have suggested co-morbidity between hypothyroidism and psychiatric disorders. However, the shared genetic etiology and causal relationship between them remain currently unclear.We assessed the genetic correlations between hypothyroidism and psychiatric disorders (anxiety disorders(ANX), schizophrenia(SCZ), major depressive disorder(MDD), and bipolar disorder(BIP)) using summary association statistics from genome-wide association studies(GWAS). Two disease-associated pleiotropic risk loci and genes were identified, and pathway enrichment, tissue enrichment, and other analyses were performed to determine their specific functions. Furthermore, we explored the causal relationship between them through Mendelian randomization (MR) analysis.We found significant genetic correlations between hypothyroidism with ANX, SCZ, and MDD, both in the Linkage disequilibrium score regression(LDSC) approach and the high-definition likelihood (HDL) approach. Meanwhile, the strongest correlation was observed between hypothyroidism and MDD(LDSC: rg=0.264, P=7.35×10 -12 ; HDL: rg=0.304, P=4.14×10 -17). We also determined a significant genetic correlation between MDD with free thyroxine(FT4) and thyroid-stimulating hormone(TSH) levels. A total of 30 pleiotropic risk loci were identified between hypothyroidism and psychiatric disorders, of which the 15q14 locus was identified in both ANX and SCZ (P values are 6.59 ×10 -11 and 2.10×10 -12 , respectively) and the 6p22.1 locus was identified in both MDD and SCZ(P values are 1.05×10 -8 and 5.75×10 -14 , respectively).Sixteen pleiotropic risk loci were identified between MDD and indicators of thyroid function, of which, four loci associated with MDD(1p32.3, 6p22.1, 10q21.1, 11q13.4) were identified in both FT4 normal level and Hypothyroidism. Further, 79 pleiotropic genes were identified using Magma gene analysis(P<0.05/18776=2.66×10 -6). Tissuespecific enrichment analysis revealed that these genes were highly enriched into six brain-related tissues. The pathway analysis mainly involved nucleosome assembly and lipoprotein particles. Finally, our two-sample MR analysis showed a significant causal effect of MDD on the increased risk of hypothyroidism, and BIP may reduce TSH normal levels.Our findings not only provided evidence of a shared genetic etiology between hypothyroidism and psychiatric disorders, but also provided insights into the causal relationships and biological mechanisms that underlie their relationship. These findings contribute to a better understanding of the pleiotropy between hypothyroidism and psychiatric disorders, while having important implications for intervention and treatment goals for these disorders.